POTRET PENGALAMAN PENDIDIKAN MULTIKULTURAL DI BENGKULU DALAM MEMBANGUN CRITICAL MULTIKULTURALISM - Rahmad Hidayat (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This study aims to see a person's behavior based on experience in the context of multicultural education in building critical multiculturalism. This type of research is a mixed method using questionnaires and focus group discussions (FGD) in collecting data. The subjects and objects are high school students in Bengkulu City. This selection is based on the consideration of high school students who are the next generation of the nation and are in the early adult human stage. The hope is that this can illustrate the role of education in its position as one of the builders of multicultural behavior. The results of this research analysis illustrate that high school students in Bengkulu City have high enough confidence to consistently interact and adapt to differences. In fact, it is not only considered a luxury, but is interpreted as a necessity where they cannot avoid cultural and religious differences. This has implications for their multicultural behavior where they are able to be smart in responding to differences. In essence, multiculturalism that was built from the experiences of high school students in Bengkulu is a final concept that builds the strength of a relationship of interaction and behavior of different ethnic, religious, racial, ethnic, cultural and religious backgrounds by creating a unity of mutual respect and respect which is classified as Critical Multiculturalism..